2022
DOI: 10.3389/fonc.2022.956593
|View full text |Cite
|
Sign up to set email alerts
|

Case report: B7-H3 CAR-T therapy partially controls tumor growth in a basal cell carcinoma patient

Abstract: B7-H3 is over-expressed in multiple types of solid tumors, making it an ideal target for chimeric antigen receptor (CAR)-T therapy. Here, we first report a case of multiple basal cell carcinoma (BCC) patient treated with humanized monoclonal anti-B7-H3 CAR-T cells through direct intratumoral injection. After three dose-escalated injections, the lesion in the abdomen decreased by 40% in volume, shrank from bulging to flat, but was not eradicated completely. The large lesion in the forehead became dry from origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In addition, there is no obvious difference in safety for these two CAR-T cell delivery strategies in the corresponding clinical research (44). Also, the therapeutic potential of local delivery pathways, such as intertumoral injection (45) and intracranial injection (46,47), has been validated in previous studies. Notably, intraventricular administrated IL-13Rα2 CAR-T cells displayed curative efficacy for patient with recurrent multifocal glioblastoma (47), suggesting the therapeutic potential of locally delivered CAR-T cells for specified tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no obvious difference in safety for these two CAR-T cell delivery strategies in the corresponding clinical research (44). Also, the therapeutic potential of local delivery pathways, such as intertumoral injection (45) and intracranial injection (46,47), has been validated in previous studies. Notably, intraventricular administrated IL-13Rα2 CAR-T cells displayed curative efficacy for patient with recurrent multifocal glioblastoma (47), suggesting the therapeutic potential of locally delivered CAR-T cells for specified tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Two major considerations of CAR design surround the optimal choice of target antigen and costimulatory domain. Among CAR-T cells targeting solid tumors, B7-H3 has emerged as a uniquely promising target, with all published results from early clinical trials all using second-generation CARs ( 40 43 ). In our experiments using in vitro killing assays with lowered transduction efficiency, we found that B7-H3.TMI.ζ CAR-T cells but not other second-generation CAR-T cells could kill three different tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biomarkers screening the dominant population benefiting from anti-B7-H3 therapy have not been defined. Several case reports implied that patients with high B7-H3 expression in tumor tissues were more likely to benefit from the anti-B7-H3 treatment 35 , 36 . We reported that TNBC patients with B7-H3 high and PD-L1 low expression face unsatisfactory therapeutic responses, urgently need novel therapies.…”
Section: Discussionmentioning
confidence: 99%